Stereotactic body radiotherapy (SBRT) for medically inoperable lung metastases—A pooled analysis of the German working group "stereotactic radiotherapy". (July 2016) - Rieber, Juliane; Streblow, Jan; Uhlmann, Lorenz; Flentje, Michael; Duma, Marciana; Ernst, Iris; Blanck, Oliver; Wittig, Andrea; Boda-Heggemann, Judit; Krempien, Robert; Lohaus, Fabian; Klass, Nathalie Desirée; et al.
Highlights: SBRT for inoperable pulmonary metastases achieved excellent LC and promising OS. LC was mainly influenced by BED at both isocenter and periphery. Important prognostic factors were identified for selecting patients for SBRT treatment. Important prognostic factors for OS were performance status, metastasis diameter and tumor histology. OS was further significantly affected by number of metastases and time interval between primary tumor diagnosis and SBRT treatment. Abstract: Objectives: The current literature on stereotactic body radiotherapy (SBRT) for oligometastatic disease is characterized by small patient cohorts with heterogeneous primary tumors, metastases location and dose regimes. Hence, this study established a multi-institutional database of 700 patients treated with SBRT for pulmonary metastases to identify prognostic factors influencing survival and local control. Materials and methods: All German radiotherapy departments were contacted and invited to participate in this analysis. A total number of 700 patients with medically inoperable lung metastases treated with SBRT in 20 centers between 1997 and 2014 were included in a database. Primary and metastatic tumor characteristics, treatment characteristics and follow-up data including survival, local control, distant metastases, and toxicity were evaluated. Lung metastases were treated with median PTV-encompassing single doses of 12.5 Gy (range 3.0–33.0 Gy) in a median number of 3 fractions (range 1–13). Results: After a median follow-up time of 14.3 months, 2-year local control (LC) and overall survival (OS) were 81.2% and 54.4%, respectively. In multivariate analysis, OS was most significantly influenced by pretreatment performance status, maximum metastasis diameter, primary tumor histology, time interval between primary tumor diagnosis and SBRT treatment and number of metastases. For LC, independent prognostic factors were pretreatment performance status, biological effective dose (BED) at PTV isocenter (BEDISO) and single fraction (PTV-encompassing) dose in multivariate analysis. Radiation-induced pneumonitis grade 2 or higher was observed in 6.5% of patients. The only factor significantly influencing toxicity was BEDISO (p = 0.006). Conclusion: SBRT for medically inoperable patients with pulmonary metastases achieved excellent local control and promising overall survival. Important prognostic factors were identified for selecting patients who might benefit most from this therapy approach.